2021
DOI: 10.3390/foods10040692
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Tubular Ceramic, Spiral Wound, and Hollow Fiber Membrane Microfiltration Module Systems for Milk Protein Fractionation

Abstract: The fractionation efficiency of hollow fiber membranes (HFM) for milk protein fractionation was compared to ceramic tubular membranes (CTM) and spiral wound membranes (SWM). HFM combine the features of high membrane packing density of SWM and the more defined flow conditions and better control of membrane fouling in the open flow channel cross-sections of CTM. The aim was to comparatively analyze the effect of variations in local pressure and flow conditions while using single industrially sized standard modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The choice of membrane materials will also impact the efficiency of the isolation. It has been found that under the same filtration conditions, the hollow fiber membrane, ceramic tubular membrane, and spiral wound membrane can be used to isolate casein and whey proteins (Schopf et al., 2021). The hollow fiber membrane has been found to have a higher isolation efficiency.…”
Section: Isolation Of Bovine β‐Caseinmentioning
confidence: 99%
“…The choice of membrane materials will also impact the efficiency of the isolation. It has been found that under the same filtration conditions, the hollow fiber membrane, ceramic tubular membrane, and spiral wound membrane can be used to isolate casein and whey proteins (Schopf et al., 2021). The hollow fiber membrane has been found to have a higher isolation efficiency.…”
Section: Isolation Of Bovine β‐Caseinmentioning
confidence: 99%
“…On the other hand, hollow fiber membranes were also utilized in food industries, such as the filtration of protein and wine. Schopf et al compared the fractionation efficiency of milk protein using hollow fiber membranes, ceramic tubular membranes, and spiral wound membranes [ 217 ]. The developed hollow fiber membrane had a high membrane packing density and low fouling tendency while maintaining excellent fractionation.…”
Section: Applications Of Hollow Fiber Membranesmentioning
confidence: 99%
“…The main industrially used module configurations are ceramic tubular membranes (CTMs), hollow-fibre membranes (HFMs) and SWMs, which all have their typical pros and cons. Compared to CTMs and HFMs, SWMs offer the highest packing density, i.e., active membrane area per module, and thus the highest whey protein mass flow per module [ 28 ]. On the contrary, SWMs suffer from flow shadows behind spacer filaments [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and, therefore, limited cleanability [ 29 ] and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%